A GIANT LOCUS FOR THE DUCHENNE AND BECKER MUSCULAR-DYSTROPHY GENE - Monaco, A; Kunkel, L (1987)
The gene responsible for Duchenne and Becker muscular dystrophy has been assigned to band Xp21 of the human X chromosome, and the isolation of DNA segments from this region has provided probes useful for prenatal diagnosis and carrier detection. It has also led to the identification and partial cloning of a large transcript that is found in skeletal muscle and potentially spans over 1.0 million basepairs of DNA. A large size for the muscular dystrophy gene locus is consistent with the observed high mutation frequency, the heterogeneity of the deletion breakpoints that are associated with the disease and the high recombination frequency of DNA markers that lie within the gene itself. © 1987.